Hybrids of Cinchona Alkaloids and Bile Acids as Antiparasitic Agents against Trypanosoma cruzi - Musikant, Alejandro Daniel (2019)
The current chemotherapy of Chagas disease needs to be urgently improved. With this aim, a series of 16 hybrids of Cinchona alkaloids and bile acids were prepared by functionalization at position C-2 of the quinoline nucleus by a radical attack of a norcholane substituent via a Barton Zard decarboxylation reaction. The antitrypanosomal activity of the hybrids was tested on different stages and strains of T. cruzi. In particular, eight out of 16 hybrids presented an IC50 ≤1 μg/mL against trypomastigotes of the CL Brener strain and/or a selectivity index higher than 10. These promising hybrids yielded similar results when tested on trypomastigotes from the RA strain of T. cruzi (discrete typing unit?DTU?VI). Surprisingly, trypomastigotes of the Y strain (DTU II) were more resistant to benznidazole and to most of the hybrids than those of the CL Brener and RA strains. However, the peracetylated and non-acetylated forms of the cinchonine/chenodeoxycholic bile acid conjugate 4f and 5f were the most trypanocidal hybrids against Y strain trypomastigotes, with IC50 values of 0.5 and 0.65 μg/mL, respectively. More importantly, promising results were observed in invasion assays using the Y strain, where hybrids 5f and 4f induced a significant reduction in intracellular amastigotes and on the release of trypomastigotes from infected cells.